VALIDITY AND PRACTICALITY OF WASAKA-BASED ETHNO-EDU MODULE IN BIOLOGY LEARNING - Ita, Ita (Journal of Banua Science Education, 2024)
Learning in the General Biology course requires relevant and contextual teaching materials to make it easier for lecturers and students to carry out the knowledge sharing process during lectures. One type of teaching material is a module. The module developed is the WASAKA-based Ethno-Edu Module. Next, to describe the quality of the module being developed, this research was carried out. This research, which aims to describe the validity and practicality of the WASAKA-based Ethno-Edu Module, was carried out using a method which is part of a series of research into the develop-ment of Educational Design Research (EDR) through expert review, one to one evaluation, small group evaluation and field test. The expert test was carried out by 7 validators whose assessment re-sults were calculated based on the Aiken formula. Individual tests, small group tests and field tests were carried out on students taking General Biology courses on the concept of Biodiversity. The re-search results obtained data on the content validity and linguistic validity of the WASAKA-based Ethno-Edu Module according to the Aiken formula ranging from 0.80-0.90 for each item. The valid-ity results of the module presentation ranged from 0.80-1.00 for each item. Student assessment of the practicality of the module was 4.29 in the individual test, 4.41 in the small group test and 4.28 in the field test. Thus, it can be concluded that the Ethno-Edu Module is classified as valid for use as a companion module in General Biology learning and is very practical for students to use.